âANALISIS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY MELALUI SUSTAINABILITY REPORT BERDASARKAN GLOBAL REPORTING INITIATIVE (Studi Kasus pada VHA Inc.) â - Bimantara, Dhimas Propana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aims to find out the level of sustainability report compliance of VHA Inc. as a form of the implementation of corporate social responsibility in based on the Global Reporting Initiative (GRI). This research uses the descriptive -qualitative method with the case study approach. This research seeks to describe the fulfillment of sustainability reporting performance from VHA Inc. based on the Global Reporting Initiative (GRI). The data source using the sustainability report of VHA Inc. VHA Inc. is a national network of nonprofit health care organization which operate in United States. The results of research that have been conducted show that the sustainability report of VHA Inc. in 2011-2012 is qualify for level B. The company has fulfilled more than 20 indicators which are had established as the minimum standard by the Global Reporting Initiative (GRI). From the sustainability report data in 2011-2012, the company show the seriousness in participate implementing the sustainable development both in the economic, environmental, and social. It is supported by some of the recognition that had been achieved by the related company of this sustainable development. Â Â Keywords: Corporate Social Responsibility, Sustainability Reporting, Global Reporting Initiative